A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.